Purification, Characterization and Antibacterial Mechanism of Plantaricin 2-1 - Mengyang LI; Xiaoxue CHE; Qingshen SUN (Shipin gongye ke-ji)
To explore the basic properties and antibacterial mechanism of bacteriocin produced by Lactobacillus plantarum L3, the strain was sub-cultured in MRS medium, and the broth was extracted by ethyl acetate extraction, followed by purification serially through dextran gel chromatography, cation exchange chromatography and reverse phase high performance liquid chromatography (RP-HPLC), and finally identified by liquid chromatography tandem mass spectrometry (LC-MS/MS). Listeria monocytogenes and Escherichia coli were used as indicator strain and the antibacterial mechanism of the plantaricin was determined by crystal violet staining, scanning electron microscopy, infrared spectroscopy, fluorescence spectroscopy, extracellular alkaline phosphatase (AKP), ATP, and lactate dehydrogenase (LDH) content analysis. Results showed that plantaricin P2-1 was a novel bacteriocin with the molecular weight of 983.564 Da. The minimum inhibitory concentration (MIC) of P2-1 against two indicator strains was 28.5 μg/mL. Plantaricin P2-1 inhibited and/or eradicate the biofilms of two indicator strains. Additionally, plantaricin P2-1 could cause the death of indicator strains by destroying cell integrity, breaking down cytoderm and cytomembrane, as indicated by leakage of AKP, ATP and LDH. Additionally, P2-1 demonstrated the ability to bind to the genomic DNA of the indicator strains, thereby disrupting their DNA structure. These results suggested that P2-1 can cause multiple damages to indicator bacteria and ultimately lead to bacterial death. The above results lay a theoretical foundation for the development and application of P2-1 as a green biological preservative.